G397(P) Hypertrophic cardiomyopathy with right and left ventricular outflow tract obstruction in a child. (May 2019) - Mallappa, A; Reddy, R; Ninjagal Shivanna, D
Abstract : Aim: To present a rare and a unique case in a 14 month old. Background: Hypertrophic cardiomyopathy with right and left ventricular outflow tract obstruction is a very rare finding. Methods: Case notes, discharge summary and operative notes were used to collect the data. Results: 14 month old was admitted with history of failure to thrive, excessive sweating, cyanosis and recurrent LRTI (lower respiratory tract infection), child had been diagnosed with congenital heart disease at 1 month of age, was on regular diuretics and beta blockers. ECHO showed severe bi ventricular outflow tract obstruction, after high risk consent underwent biventricular myectomy. Conclusion: Intraoperatively noted to have grossly hypertrophied ventricles with evidence of systolic anterior motion of mitral valve and a single abnormal fibrous band from papillary muscle to left ventricular outflow tract. Post- operatively stay was uneventful in ITU was discharged on 10th post operative day with regular follow up.